Alpha and beta-Thalassemia mutations in Hubei area of China - Yaowu Zhu; Na Shen; Xiong Wang; Juan Xiao; Yanjun Lu (BMC, 2020)
Abstract Background Thalassemia is a group of inherited hemoglobic disorders resulting from defects in the synthesis of one or more of the hemoglobin chains, which is one of the most prevalent inherited disorders in southern China. Only few studies reported the molecular characterization of α- and β-Thalassemia in Hubei Province in the central of China. Methods A total of 4889 clinically suspected cases of thalassemia were analyzed by Gap-PCR, PCR-based reverse dot blot (RDB). Results 1706 (33.8%) subjects harbored thalassemia mutations, including 539 (11.0%) subjects with α-thalassemia, 1140 (23.3%) subjects with β-thalassemia mutations, and 25 (0.51%) subjects with both α- and β-thalassemia mutations. Seven genotypes of α-thalassemia mutations and 29 genotypes of β-thalassemia mutations were characterized. --SEA/αα (66.05%), −α3.7/αα (24.12%), and -α4.2/αα (3.71%) accounted for 93.88% of the α-thalassemia mutations. βIVS-II-654/βN, βCD41-42/βN, βCD17/βN, βCD27-28/βN, βCD71-72/βN, β − 28/βN, β − 29/βN, βCD43/βN, βE/βN, accounting for 96.40% of all β-thalassemia genotypes. Furthermore, mean corpuscular volume (MCV) and mean corpuscular Hb (MCH) were sensitive markers for both β-thalassemia and α-thalassemia with --SEA/αα, but not -α3.7/αα and -α4.2/αα. Conclusions: Our data indicated great heterogeneity and extensive spectrum of thalassemias in Hubei province of China.